A view on EGFR-targeted therapies from the oncogene-addiction perspective - Perez, Rolando; Crombet, Tania; de Leon, Joel; Moreno, Ernesto (Frontiers in Pharmacology, 2013)
Tumor cell growth and survival can often be impaired by inactivating a single oncogen – a phenomenon that has been called as 'oncogene addiction'. It is in such scenarios that molecular targeted therapies may succeed. Among known oncogenes, the epidermal growth factor receptor (EGFR) has become the target of different cancer therapies. So far, however, the clinical benefit from EGFR-targeted therapies has been rather limited. A critical review of the large amount of clinical data obtained with anti-EGFR agents, carried out from the perspective of the oncogene addiction concept, may help to understand the causes of the unsatisfactory results. In this article we intend to do such an exercise taking as basis for the analysis a few case studies of anti-EGFR agents that are currently in the clinic. There, the 'EGFR addiction' phenomenon becomes apparent in high-responder patients. We further discuss how the concept of oncogene addiction needs to be interpreted on the light of emerging experimental evidences and ideas; in particular, that EGFR addiction may reflect the interconnection of several cellular pathways. In this regard we set forth several hypotheses; namely, that requirement of higher glucose uptake by hypoxic tumor cells may reinforce EGFR addiction; and that chronic use of EGFR-targeted antibodies in EGFR-addicted tumors would induce stable disease by reversing the malignant phenotype of cancer stem cells and also by sustaining an anti-tumor T cell response. Finally, we discuss possible reasons for the failure of certain combinatorial therapies involving anti-EGFR agents, arguing that some of these agents might produce either a negative or a positive trans-modulation effect on other oncogenes. It becomes evident that we need operational definitions of EGFR addiction in order to determine which patient populations may benefit from treatment with anti-EGFR drugs, and to improve the design of these therapies.